Operationalizing triple bottom line harvest strategies. (27th March 2020) - Dichmont, Catherine M; Dowling, Natalie A; Pascoe, Sean; Cannard, Toni; Pears, Rachel J; Breen, Sian; Roberts, Tom; Leigh, George M; Mangel, Marc
Abstract: Over the past 50 years, the diversity of fisheries types being actively managed has changed from mainly data-rich, industrial sectors to more socially, economically, and environmentally complex multispecies and multisector fisheries. Accompanying this change has been a broadening of management objectives to include social and economic considerations with traditional resource sustainability objectives, the so-called triple bottom line, and the need to include these considerations into harvest strategies. The case of a line fishery in Australia's Great Barrier Reef is used as a demonstration of the first steps in implementing triple bottom line harvest strategies. This fishery has several disparate sectors including commercial, tourism, and recreation; targets multiple but important reef species; and is undertaken in a World Heritage Site. This work highlights the need for a much-expanded set of objectives elicited from stakeholders that are either included in the trade-off analyses of the different harvest strategies or directly in an optimization. Both options demonstrated that a paradigm shift is required to emphasize representative participatory management systems that assemble teams from quite different backgrounds and viewpoints; use much broader set of objectives; and modify tools and (especially) the data collected within revised monitoring programmes to underpin these tools.